Implikasi Kekeliruan Substansi Permohonan Penetapan Pengadilan terhadap Kedudukan Hukum Anak Luar Kawin - Rachmadhiva, Affra Sabilla; Setyorini, Hening Hapsari (Universitas Batanghari Jambi, 2025)
This study analyzes the implications of substantive errors in court petitions regarding the recognition and legitimization of extramarital children, focusing on enhancing their legal status following the death of the biological father. Based on a case study of Pontianak District Court Determination No. 246/Pdt.P/2021/PN Ptk, it was found that inaccuracies in the substance of the petition can result in ambiguous legal determinations, particularly regarding the child’s status as a recognized but not fully legitimate child. This ambiguity impacts the civil rights of extramarital children, including inheritance rights from their biological father. This research employs doctrinal legal methodology with a descriptive-analytical approach through a literature review, aiming to comprehensively explain the court’s essential role in ensuring the completeness of petition substance from the initial stages, especially at Meja I (Desk I). The findings emphasize the importance of legitimizing extramarital children to secure a stronger legal status equivalent to legitimate children, ensuring the protection of civil rights and reducing the potential for future legal conflicts.